2013
DOI: 10.1097/ccm.0b013e31827bfc3c
|View full text |Cite
|
Sign up to set email alerts
|

Using Existing Data to Address Important Clinical Questions in Critical Care

Abstract: Objective With important technological advances in healthcare delivery and the internet, clinicians and scientists now have access to overwhelming number of available databases capturing patients with critical illness. Yet investigators seeking to answer important clinical or research questions with existing data have few resources that adequately describe the available sources and the strengths and limitations of each. This article reviews an approach to selecting a database to address health services and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 114 publications
0
57
0
Order By: Relevance
“…Interest in observational research is driven by legislation promoting comparative effectiveness research (e.g., the Affordable Care Act) (3), the emergence of large administrative and electronic healthcare record databases offering data mining opportunities (4,5), and the development and adoption of novel statistical methods for analyzing observational data. Many of these methods, such as propensity scores (PSs) and other exposure modeling methods, attempt to emulate aspects of RCTs and can reduce confounding in studies with nonrandom treatment assignment (6).…”
mentioning
confidence: 99%
“…Interest in observational research is driven by legislation promoting comparative effectiveness research (e.g., the Affordable Care Act) (3), the emergence of large administrative and electronic healthcare record databases offering data mining opportunities (4,5), and the development and adoption of novel statistical methods for analyzing observational data. Many of these methods, such as propensity scores (PSs) and other exposure modeling methods, attempt to emulate aspects of RCTs and can reduce confounding in studies with nonrandom treatment assignment (6).…”
mentioning
confidence: 99%
“…Prior studies investigating ED revisits have found multiple associated factors, including advanced age, 8 higher triage acuity, 8 and lack of access to primary care. 9 However, administrative and other claims data often lack clinical data at the patient level, limiting the value of such research to provider organizations and clinicians; 10 it is unclear in which direction this influences these results. Large electronic health records offer the opportunity to integrate previously disparate data sources, enabling analyses that seek to identify the complex linkages between clinical details and resource utilization.…”
mentioning
confidence: 99%
“…Nevertheless, our study has some limitations that merit consideration. First, this was a retrospective claims database analysis, so there was the possibility of residual confounding (20,21). Second, we did not have information on the severity index of acute illness such as Acute Physiology and Chronic Health Evaluation II or Sequential Organ Failure Assessment scores.…”
Section: Discussionmentioning
confidence: 99%